Cardiovascular risk factors - Vrablik, Michal (Henry Stewart Talks, 2008)
Cardiovascular disease burden, Atherosclerosis as a cause of CVD, Non-modifiable and modifiable risk factors for CVD, Dyslipidemia and CVD risk, Apoproteins as CVD risk predictors, Quality of lipoprotein particles as an important indicator of lipids associated risk, Smoking as a CVD risk factor, Diabetes as a risk factor for CVD, Metabolic syndrome and CVD risk, Risk assessment tools, Atherosclerosis imaging techniques and risk assessment